MCM4 is a novel prognostic biomarker and promotes cancer cell growth in glioma - Yang, Shu; Yuan, Yixiao; Ren, Wenjun; Wang, Haiyu; Zhao, Zhong; Zhao, Heng; Zhao, Qizhe; Chen, Xi; Jiang, Xiulin; Zhang, Lei (Frontiers in Oncology, 2022)
Gliomas account for 75% of all primary malignant brain tumors in adults and result in high mortality. Accumulated evidences have declared the minichromosome maintenance protein complex (MCM) gene family plays a critical role in modulating the cell cycle and DNA replication stress. However, the biological function and clinic characterization of 9 MCM members in low-grade glioma are not yet clarified. In this study, we utilized diverse public databases, including The Cancer Genome Atlas (TCGA), Chinese Glioma Genome Atlas (CGGA), Rembrandt, Human Protein Atlas (HPA), Linkedomics, cbioportal, Tumor and Immune System Interaction Database (TISIDB), single-sample GSEA (ssGSEA), Tumor Immune Estimation Resource (TIMER), Genomics of Drug Sensitivity in Cancer (GDSC) and Cancer Therapeutics Response Portal databases to explore the mRNA and protein expression profiles, gene mutation, clinical features, diagnosis, prognosis, signaling pathway, tumor mutational burden (TMB), immune subtype, immune cell infiltration, immune modulator and drug sensitivity of 9 MCMs. Afterward, qRT-PCR was utilized to detect the expression of the MCM family in glioblastoma multiforme (GBM) cells lines. The 1-, 3-, or 5-year survival rate was predicted by utilizing a nomogram established by cox proportional hazard regression. In this study, we found that 9 MCMs were consistently up-regulated in glioma tissues and glioma cells lines. Elevated 9 MCMs expressions were significantly correlated with a higher tumor stage, isocitrate dehydrogenase (IDH) mutates, 1p/19q codeletion, histological type, and primary therapy outcome. Survival analyses showed that higher expression of MCM2-MCM8 and MCM10 were linked with poor overall survival (OS) and progression-free survival (PFS) in glioma patients. On the other hand, up-regulated MCM2-MCM8 and MCM10 were significantly associated with shorter disease-specific survival (DSS) in glioma patients. Univariate and multivariate analyses revealed that MCM2, MCM4, MCM6, MCM7 expression and tumor grade, 1p/19q codeletion, age, and primary therapy outcome were independent factors correlated with the clinical outcome of glioma patients. More importantly, a prognostic MCMs model constructed using the above five prognostic genes could predict the overall survival of glioma patients with medium-to-high accuracy. Furthermore, functional enrichment analysis indicated that MCMs principal participated in regulating cell cycle and DNA replication. DNA